Hazard classification of toluene, methane and carbon dioxide for bomb detection using fuzzy logic - MacAsaet, Dailyne (Animo Repository, 2019)
This paper intends to explore bomb detection technology by employing fuzzy logic in classifying Toluene, Carbon dioxide and Methane which are commonly used gases in bombs and other flammables. This research uses Matlab Fuzzy Logic toolbox in classifying gases into three hazard classifications- Safe, Hazardous, and Deadly based on gas concentration and exposure time. Provided in this paper are the standard gas levels which are considered safe to human with respect to exposure time. The output of the classification will help develop a more improved and accurate bomb detection system which is of great importance in today's world.